Enunciation and denunciation of power in a few Black African novels of the post independence era - (:unkn) unknown (My University, 2010)
The black African novel of denunciation which is called the subversive novel and which some insert in the category said to be the novel of rupture, as a macro act of language, does involve a subversive and illocutory aim. That is true even if the post independence black African literary discourse, like any discourse, remains under constraint, that is to say, determined to a large extent, by the socio-political context, but also, the literary field where various positionings and postures of authors are in competition. In this work, we endeavour to show that this aim which is an attempt to reveal the awkwardness of the new political and/or religions systems, a result of the relationship between a non verbal black African context and the internal side of novels and results in literary construction of various individual and collective ethos, can be studied through the discourse analysis method. By linking the external and inner side of the literary text, which moves aside the str ucturalist immanence. We tackle the post independence black African novel as a system of enunciation whose deistic and modal centre vouches for the discourse, that is to say the principal narrator who is the most often homodiectic in our corpus except Perpetue where he is extradiegetic. So, the thesis ruins the romantic conception which distinguishes the social self from the creative self. We hence consider that the novels of our corpus are social activities involved in discursive practices of a society, which definitely settles the relationship between a text and society raising the notions of the enunciation issue with a broad socio cultural scope like the scenography, the generic scene, the validated scene, the paratopy,… we hence confirm the possibility of a rupture in the black African literary approaches considering literary history made up of three separate different entries(Man, his work and the environment) which have remained more or less classical, that is to say them
Keywords: African Research